TRANSPLANTATION OF HEPATOCYTES AS THE METHOD OF TREATMENT OF LIVER FAILURE: EXPERIMENTAL AND CLINICAL EXPERIENCE - M. Y. Shagidulin; N. A. Onishchenko; M. E. Krasheninnikov (Вестник трансплантологии и искусственных органов, 2010)
For correction and treatment of liver failure before liver transplantation were proposed severe methods such as: extracorporal devices, transplantation of hepatocytes and implanted tissue-engineering units. The function of healthy hepatocytes presumes to stabilize the state of patients with chronic liver diseases and to wait a donor organ transplantation. In this review the results of experimental and clinical therapy of liver diseases by method of hepatocyte transplantation were summarized.